Geospatial mapping of groundwater potential zones using multi-criteria decision-making AHP approach in a hardrock basaltic terrain in India - Arjun B. Doke (Elsevier, 2021)
Among all other natural resources, groundwater is one of the most essential for environmental, biological, and socioeconomic activities. Several factors such as geology, distance from the river, geomorphology, slope, land-use, drainage density, lineament density, soil, and rainfall influence groundwater recharge and its availability. In this study, an integrated approach of Geographical Information System (GIS) based Multi-Criteria Decision Making (MCDM), Analytical Hierarchy Process (AHP), and remote sensing were used for geospatial mapping of groundwater. For the determination of influencing factors, an extensive literature review was considered to form a pairwise comparison matrix (PCM) and calculate the weight of each factor. The scores of the sub-parameters were also assigned based on published literature, and after that, the weighted overlay analysis (WOA) tool in ArcGIS10.1 was used to produce the final groundwater potential map. About 14% (684 km2) of the study area is recognized as ‘high groundwater potential zone’, 34% (1591 km2) in ‘moderate groundwater potential zone’, 27% (1291 km2) in ‘low groundwater potential zone’ and the remaining 24% (1141 km2) in ‘poor groundwater potential zone’. In the accuracy assessment, the groundwater potential zones i.e. high, moderate, and poor in suitability map is precisely estimated contrasting to the zone ‘low’ in the producer’s point of view, but high and poor groundwater zones detected more precisely compared to others in user’s point of view. The methodology, techniques, and results of the current investigation may be useful to evaluate the groundwater potential zone in similar drought-prone regions around the world.